FoxP3-Positive T-Regulatory Cells in Lymph Nodes with Mycosis Fungoides and Sézary Syndrome. (11th November 2014) - Bhat, Rekha; Khandpur, Bhavna; Vonderheid, Eric C.; Hou, J. Steve
Abstract : Mycosis fungoides and Sézary syndrome are indolent cutaneous T-cell lymphomas, with skin-associated peripheral lymph nodes being the most frequent extracutaneous site of involvement. Acquisition of functional properties of regulatory T-cells by malignant T-cells in advanced disease may contribute to immunosuppression. Whereas previous studies examining FoxP3 protein expression in mycosis fungoides and Sézary syndrome have focused on skin specimens, little data are available on lymph nodes from patients with these conditions. In this study we examined FoxP3+ regulatory T-cells in lymph nodes from 26 patients with mycosis fungoides and Sézary syndrome and correlated the findings with clinical data, molecular assays for T-cell clonality, and flow cytometry. Except for one case of Sézary syndrome in which malignant T-cells expressed FoxP3 protein, a significantly lower number of FoxP3-expressing cells occurred in lymph nodes that were clearly involved with lymphoma as compared to uninvolved nodes. Cox proportional hazards model showed that lymph node rating and histological evidence of transformation, but not number of FoxP3+ cells, were factors significantly associated with adverse prognosis. We speculate that modulation of FoxP3+ cells in lymph nodes involved with lymphoma might play a role in disease progression. Attainment of a regulatory T-cell phenotype by a subset of lymphoma cells might signal a poor prognosis.